Implementation of Outcome-Based Education from the Perception of Lecturers and Students - Handayani, Naniek Utami; Wibowo, M. Agung; Christiani, Skolastika D. K.; Ulkhaq, M. Mujiya (Universitas Pendidikan Ganesha, 2024)
Outcome-based education (OBE) means clearly focusing and organizing everything in an educational system around what is essential for all students to be able to do successfully at the end of their learning experiences. This means starting with a clear picture of what is important for students to be able to do, then organizing curriculum, instruction, and assessment to make sure this learning ultimately happens. Therefore, this study aims to analyze the perceptions of lecturers and students regarding the implementation of OBE in the Faculty of Engineering. There are six variables used in this study, i.e., statement of student’s achievement, relevance of student’s achievements, subject’s preparation, teaching and learning process, supporting facilities, and evaluation. The indicators are generated according to the literature review and interview with experts, resulting 51 indicators. There are 103 students and 79 lecturers to be selected as the respondents. The respondents are asked about their opinions regarding the OBE implementation according to those indicators. Results show that from the perspective of lecturers, OBE is very well implemented regarding the variables of statement of student’s achievement, relevance of student’s achievements, and teaching and learning process; while the others are well implemented. However, from the perspective of students, OBE is fairly implemented regarding the variable of supporting facilities; while the others are well implemented.